Association between suicides among females and phase of uterine cycle during autopsy at a tertiary care centre in Bengaluru north - Udaya Shankar , B S; Sujatha, P L; Shivakumar, B C; Vijaya , C (Journal of Indian Academy of Forensic Medicine, 2021)
The study of “Association between suicides among females and phase of uterine cycle during autopsy” was carried out at a tertiary  care centre over a period of 5 years with aim to identify the phase of uterine cycle in female suicides and to correlate the phase of  uterine cycle with methods and reasons of suicide. A total of 222 cases fulfilled criteria, most vulnerable age group was 21-30 years  (112 cases) and most vulnerable phase of uterine cycle was menstruation phase-88 cases (40%) followed by secretory phase-68 cases  (31%). Most female suicides (79%) were due to hanging. Majority of suicidal cases during the 11–20-year (24 cases) and 21–30-year  (50 cases) age groups were menstruating. In contrast, majority of suicidal cases during the 31–40-year (13 cases) and 41–50-year (8  cases) age groups were in secretory phase. Dysmenorrhoea (13 cases) and stomach pain (9 cases) were the reasons for the suicide  exclusively in menstruating women, whereas depression (12 cases) was seen more in secretory phase and husband related conflicts  were almost equally distributed in secretory (10 cases) and menstrual (9 cases) phases. Thus, this study indicates the time of applying  the various strategies to curb the unhealthy emotional state of a woman in the form of health education, counseling and treatment of  PMTS, a period between 4 days prior to start of menses to the end of menstruation; wherein a woman is vulnerable for sadness and  impulsive acts.
Keywords: Suicide; Uterine cycle; PMS; PMDD; Menstruating; Secretory